The Architecture of Collapse: Applying Modern Systems Theory to the Institutional Fragility of the Mali Empire: A Historical Case Study in Leadership Dependency, Operational Fragility, and Institutional Durability - Glushak, Natalia (International Journal of Business and Social Science Research, 2026)
This article introduces the Glushak Institutional Durability Framework (IDF), a seven-dimension diagnostic model for evaluating organizational resilience and founder dependency in construction enterprises and complex service organizations. The framework is derived from a systems-theory analysis of one of history's most precisely documented cases of high-performing institutional collapse: the reign of Mansa Musa I of the Mali Empire (r. 1312–1337), whose extraordinary achievements dissolved within a century of his death. The analysis demonstrates that the collapse was caused not by external military or economic pressure but by six identifiable systems-design failures-founder-concentrated authority, unstructured capital deployment, patronage-dependent knowledge infrastructure, absent succession systems, undistributed accountability, and the erosion of informal governance without formal protection. From this historical evidence, the IDF is derived as a transferable diagnostic instrument applicable to modern construction firms, project-based enterprises, and founder-led service organizations. The IDF moves beyond the Great Man Theory of leadership and posits that organizational durability is a function of systemic redundancy: by replacing individual instinct with evidence-based frameworks and codified governance, operational excellence becomes an institutional trait rather than a personal one. The article further demonstrates the IDF's application to the residential construction sector, where founder dependency is a structural industry condition producing measurable operational fragility. It introduces a proprietary operational framework developed by the author as the operational implementation of the IDF's governance principles at the project level, arguing that together the IDF and the framework constitute a two-level original contribution to construction governance: the IDF operating as a diagnostic instrument at the organizational level, and the framework operating as a governance architecture at the project delivery level. Methodological limitations of the historical case method are acknowledged explicitly.